Analisis Kemampuan Koneksi Matematis Ditinjau Dari Kesulitan Siswa Menyelesaikan Soal Matematika Pada Generasi Alpha Di Min 7 Kuningan - Firda Halawati; Rahmi Hidayati (Jurnal Elementaria Edukasia, 2023)
Mathematics has a higher level of difficulty and abstractness of concepts compared to other subjects. This can be seen from the low ability of mathematical connections. This research aims to determine students' mathematical connection abilities, determine students' difficulties in solving mathematics problems, and determine students' mathematical connection abilities in terms of students' difficulties in solving mathematics problems. This research is a qualitative research. The subjects in this study were 6 students who were categorized into 2 high ability students, 2 medium ability students and 2 low ability students. The data collection techniques used were tests, interviews and documentation. The results of this research show that mathematical connection abilities are seen from the indicators of understanding the relationship between representations of the same concepts and procedures, recognizing and using connections between mathematical ideas, and using mathematics in everyday life. Students' difficulties in solving mathematics problems are based on high ability students: having difficulty using concepts, finding information in mathematical models and having difficulty calculating. Medium ability students experience difficulties: solving verbal problems, difficulty understanding concepts and principles. Low ability students experience difficulties: solving verbal problems, understanding concepts and procedures, difficulty using principles in calculating